Sustainability Of Jabotabek-Indonesia: Lessons Learned From The Asian Crisis - BS Kusbiantoro (The Institute for Research and Community Services, Institut Teknologi Bandung, 1999)
The Asian crisis shows how Jabotabek's previous rapid development is not sustainable. Development based on Jabotabek's comparative advantages should be reevaluated. For instance, industrial development relied on high import contents and cheap labor is very vulnerable to the global forces; insensitivity to integrated local community development contributes to social unrest; lack of supporting infrastructure degrades the environment all of this makes Jabotabek less sustainable economically, socially, and environmentally.